Implementasi Kebijakan Pendidikan Terhadap Kebijakan Publik - Grascyella Cintiya Marito; Niken Larasati; Rizka Fitri Aulia Lubis; Erinaldi, Erinaldi (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
Education policy is a strategic part of public policy that aims to create a fair, equitable and quality education system. The implementation of education policy is a crucial stage that determines the achievement of the policy objectives that have been formulated. This journal was created to find out the process of implementing education policy in the context of public policy in Indonesia, as well as to identify supporting and inhibiting factors in its implementation. The method used is qualitative through journal literature studies. The results of the study show that the effectiveness of education policy implementation is greatly influenced by institutional factors, human resource capacity, coordination between stakeholders, and community participation. Challenges such as regional inequality, budget limitations and suboptimal bureaucracy are the main obstacles in policy implementation. Therefore, strong integration is needed between policy formulation and implementation, as well as the improvement of governance systems that are Transparent, Accountable and Adaptive to social dynamics. This journal was created to show that a collaborative approach in the implementation of education policy as part of efforts to strengthen public policies oriented towards service and social justice